Why and How to Use Narratives for Stakeholder Engagements? - Heinonen, Sirkka; Viitamäki, Riku; Virmajoki, Veli (Finland, 2026)
This policy brief presents a set of four radical narratives embedded in the future world of digital and green transformation. These narratives of futures hybrid workers reflect a new paradigm of work as it emerges based on our research findings. We highlight the role, importance and potential of narratives and the narrative foresight niche of futures studies. We pay special attention to the “why and how” of communicating narratives to stakeholders. Our narratives are meant to inspire imagination and open vistas to possible futures of worklife.